French post-war social theory international knowledge transfer - Robbins, Derek (Los Angeles ; London : SAGE, 2012)
"French social and philosophical thought has played a very significant role in the development of European and American social theory. This detailed, timely book provides a map of the production and reception of French social thought within a global sociological context. Critically comparing the work of five key theorists Derek Robbins examines how their ideas were produced and received before persuasively setting out the key differences between their philosophical and ideological positions. The book sensitively traces the cross-currents of social theory and confidently leads the reader through the complex foundations of Western social thought. Each chapter represents a textual analysis of the production of a critical intellectual and focuses upon the work of: Althusser, Foucault, Aron, Lyotard, Bourdieu. This carefully crafted volume represents a significant contribution to the globalization of theory and will be essential reading for anyone interested in Western social theory and the foundations of sociological thought."--Publisher's website.
Introduction -- Raymond Aron (1905-83) -- Louis Althusser (1918-90) -- Michel Foucault (1926-84) -- Jean-Franc̜ois Lyotard (1924-98) -- Pierre Bourdieu (1930-2002) -- Preliminary concluding comments.
Includes bibliographical references and index.
Keywords: Sociology -- France -- History -- 20th century; Social sciences -- France -- Philosophy; Sociologists -- France -- History -- 20th century